2020
DOI: 10.1371/journal.pone.0239411
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas9-mediated correction of mutated copper transporter ATP7B

Abstract: Wilson's disease (WD) is a monogenetic liver disease that is based on a mutation of the ATP7B gene and leads to a functional deterioration in copper (Cu) excretion in the liver. The excess Cu accumulates in various organs such as the liver and brain. WD patients show clinical heterogeneity, which can range from acute or chronic liver failure to neurological symptoms. The course of the disease can be improved by a lifelong treatment with zinc or chelators such as D-penicillamine in a majority of patients, but s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…The field of medical research focused on utilizing the CRISPR/Cas9 system for gene editing therapies is experiencing rapid growth. It is increasingly recognized for its prominent role in addressing diseases with complex etiologies like DMD [147] , liver diseases [148] , and retinal diseases [80] . DMD is a genetic muscle disease caused by mutations in the DMD gene located on the X chromosome [149 , 150] .…”
Section: Biomedical Applications Of Crispr/cas9 Systemmentioning
confidence: 99%
“…The field of medical research focused on utilizing the CRISPR/Cas9 system for gene editing therapies is experiencing rapid growth. It is increasingly recognized for its prominent role in addressing diseases with complex etiologies like DMD [147] , liver diseases [148] , and retinal diseases [80] . DMD is a genetic muscle disease caused by mutations in the DMD gene located on the X chromosome [149 , 150] .…”
Section: Biomedical Applications Of Crispr/cas9 Systemmentioning
confidence: 99%
“…Indications for liver transplantation (LT)[ 67 ] in patients with WD are those with ALF, as defined by the rapid development of severe hepatic insufficiency with coagulopathy and with hepatic encephalopathy, with progression of liver dysfunction to liver failure despite drug therapy, and those with acute on chronic liver failure due to WD. [ 1 17 43 ] LT in patients with neurologic WD is still controversial.…”
Section: Treatmentmentioning
confidence: 99%
“…[ 72 73 74 75 ] A recent study reported the use of CRISPR/Cas9 technology to correct ATP7B point mutation frequently detected in WD patients. [ 67 ] However, clinical studies for WD gene modification are required so that these could become alternative curative strategies in the future.…”
Section: Treatmentmentioning
confidence: 99%
“…Pöhler and colleagues showed that CRISPR-Cas9 technology is efficient not only in introducing specific ATP7B mutations but also in correcting ATP7B point mutations [ 211 ]. Although the single-stranded oligo DNA nucleotide (ssODN) is limited to non-viral delivery methods, such application can lead to direct and safe modification in the point mutations within the ATP7B gene, providing therapeutic potential [ 212 ].…”
Section: Wilson Diseasementioning
confidence: 99%